Interrupting Chagas disease transmission in Venezuela A interrupção da transmissão da doença de Chagas na Venezuela - Alberto ACHÉ (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
The interruption of vectorial transmission of Chagas disease in Venezuela is attributed to the combined effects of ongoing entomoepidemiological surveillance, ongoing house spraying with residual insecticides and the concurrent building and modification of rural houses in endemic areas during almost five decades. The original endemic areas which totaled 750,000 km², have been reduced to 365,000 km². During 1958-1968, initial entomological evaluations carried out showed that the house infestation index ranged between 60-80%, the house infection index at 8-11% and a house density index of 30-50 triatomine bugs per house. By 1990-98, these indexes were further reduced to 1.6-4.0%, 0.01-0.6% and 3-4 bugs per house respectively. The overall rural population seroprevalence has declined from 44.5% (95% C.I.: 43.4-45.3%) to 9.2% (95% C.I.: 9.0-9.4%) for successive grouped periods from 1958 to 1998. The annual blood donor prevalence is firmly established below 1%. The population at risk of infection has been estimated to be less than four million. Given that prevalence rates are stable and appropriate for public health programmes, consideration has been given to potential biases that may distort results such as: a) geographical differences in illness or longevity of patients; b) variations in levels of ascertainment; c) variations in diagnostic criteria; and d) variations in population structure, mainly due to appreciable population migration. The endemic areas with continuous transmission are now mainly confined to piedmonts, as well as patchy foci in higher mountainous ranges, where the exclusive vector is Rhodnius prolixus. There is also an unstable area, of which landscapes are made up of grasslands with scattered broad-leaved evergreen trees and costal plains, where transmission is very low and occasional outbreaks are reported. A interrupção da transmissão da doença de Chagas é atribuida aos efeitos conjuntos da vigilância soroepidemiológica, borrifação contínua de inseticidas residuais assim como a construção e modificação de casas rurais nas áreas endêmicas nas últimas cinco décadas. Os 750.000 km² originais da área endêmica foram reduzidos a 365.000 km². Durante os anos 1958 a 1968, avaliações entomológicas iniciais indicaram que o índice de infestação domiciliar variava de 60 a 80%, o índice de infeção domiciliar entre 8 e 11% e o índice de densidade domiciliar de 30 a 50 triatomíneos por casa. Para o período 1990 a 1998 estes índices foram respectivamente reduzidos para 1,6 a 4,0%, 0,01 a 0,6% e 3 - 4 triatomíneos por casa. A soroprevalência geral diminuiu de 44,5% (95% I.C.: 43,4 a 45,3) para 9,2% (95% I.C.: 9,0 a 9,4%) entre 1958 a 1998. A prevalência da infecção pelo Trypanosoma cruzi entre os doadores de sangue encontra-se abaixo de 1%. A população sob risco de infecção tem sido estimada em menos de quatro milhões de pessoas. Tendo em vista que as taxas de prevalência são estáveis e apropriadas para a avaliação de programas de saúde pública, atenção tem sido dada para tendências potenciais que poderiam alterar o sentido dos resultados tais como: diferenças geográficas na doença ou na longevidade dos pacientes; variações nos níveis de determinação; variações nos critérios de diagnóstico; e variações nas estruturas populacionais, assim como migrações significantes de populações. As áreas endêmicas com transmissão contínua estão restritas a sopés de montes e focos isolados em áreas montanhosas, onde o vetor exclusivo é Rhodnius prolixus. Existem ainda áreas onde a transmissão é muito baixa e ocorrem surtos ocasionais com poucos casos agudos notificados nos estados de Barinas e Portuguesa.